2022
DOI: 10.5194/acp-2022-614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of variable, ice-ocean surface properties and air mass transformation on the Arctic radiative energy budget

Abstract: Abstract. Low-level airborne observations of the Arctic surface radiative energy budget are discussed. We focus on the terrestrial part of the budget, quantified by the thermal-infrared net irradiance (TNI). The data have been collected in cloudy and cloud-free conditions over and in the vicinity of the marginal sea ice zone (MIZ) close to Svalbard during two aircraft campaigns in spring of 2019 and in early summer of 2017. The measurements, complemented by ground-based observations available from the literatu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Turbulent fluxes are not provided in the dataset. This is left for the data user and can follow the examples given in 18,31,32 . We stress that only such flight sections should be considered for the derivation of turbulent fluxes where the aircraft is flying in a straight line.…”
Section: Cgr-4mentioning
confidence: 99%
“…Turbulent fluxes are not provided in the dataset. This is left for the data user and can follow the examples given in 18,31,32 . We stress that only such flight sections should be considered for the derivation of turbulent fluxes where the aircraft is flying in a straight line.…”
Section: Cgr-4mentioning
confidence: 99%
“…In consequence, a realistic representation of the impact of clouds within the Arctic climate system in numerical weather and climate models appears crucial. In particular, the radiative energy budget (REB) of the surface and the atmosphere is largely determined by the presence and properties of clouds (Wendisch et al, 2022b). The REB is quantified by the difference of downward and upward irradiances, F ↓ and F ↑ , respectively; it is referred to as net irradiance F net , with:…”
Section: Introductionmentioning
confidence: 99%
“…In summer, no significant differences were found. Since the temporal dependence of the thermodynamic adjustments to cloud dissipation complicates an accurate and continuous quantification of this effect (Walsh and Chapman, 1998;Wendisch et al, 2022b), differences between both approaches will remain and likely depend on cloud type, season, and surface conditions. In contrast, the conceptual differences resulting from the cloud-induced surface albedo change can be reduced for the radiative-transfer approach.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ABL does not develop a residual layer due to the absence of a diurnal cycle for most of the year, and even during the polar day, convection typically plays a minor role (Persson et al, 2002;Tjernström and Graversen, 2009;Morrison et al, 2012;Brooks et al, 2017). Within this study, we refer to two typical states of the Arctic ABL observed over sea ice in winter and early spring: a cloudless ABL with a surface-based temperature inversion and a cloudy ABL with pronounced cloud-top inversion (Tjernström and Graversen, 2009;Stramler et al, 2011;Morrison et al, 2012;Wendisch et al, 2023b). We have distinguished between those two states of the atmosphere, as many models have difficulties reproducing the bimodal distribution of the terrestrial radiation (Solomon et al, 2023).…”
Section: Introductionmentioning
confidence: 99%